2021
DOI: 10.3390/app11178010
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Additive Manufacturing of Inconel 718 Superalloy

Abstract: Inconel 718 is a nickel-based superalloy and an excellent candidate for the aerospace, oil, and gas industries due to its high strength and corrosion resistance properties. The machining of IN718 is very challenging; therefore, the application of additive manufacturing (AM) technology is an effective approach to overcoming these difficulties and for the fabrication of complex geometries that cannot be manufactured by the traditional techniques. Selective laser melting (SLM), which is a laser powder bed fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…A high microhardness value of 460.5 HV was achieved in the as-fabricated IN718 sample built on top of a pin support structure. The results were comparable with the LPBF IN718 in the literature for as-fabricated LPBF sample (322 HV) [21], heat-treated LPBF (335 HV), heat-treated plus hot isostatic pressing (478 HV) [37], and as-fabricated wrought and cast (353 HV) [37].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A high microhardness value of 460.5 HV was achieved in the as-fabricated IN718 sample built on top of a pin support structure. The results were comparable with the LPBF IN718 in the literature for as-fabricated LPBF sample (322 HV) [21], heat-treated LPBF (335 HV), heat-treated plus hot isostatic pressing (478 HV) [37], and as-fabricated wrought and cast (353 HV) [37].…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, at a relatively high value of the laser power (P), Parimi et al [20] observed increased numbers of entrapped bubbles within the melt pools, thus a decreased level of density. Ravichander et al [21] conducted a comprehensive study on the effect of laser processing parameters on the geometry accuracy of the as-fabricated sample. Out of all other energy density parameters (laser power (P), hatch spacing (h), and layer thickness (t)), they found laser scan speed (v) as a dominant factor towards grain length, which affects the final dimension of the part.…”
Section: Introductionmentioning
confidence: 99%
“…Additive Manufacturing (AM) can offer highly complex parts with minor post-processing operations [9][10][11]. AM is a developing technology that can produce parts from 3D CAD models, as defined by ISO/ASTM 52900 [12].…”
Section: Introductionmentioning
confidence: 99%
“…An artificial neural network (ANN) is a computational system that uses a network of functions (nodes) to process data input into a desired output. It was inspired by the biological nervous system; therefore, the network is composed of interconnected elements (nodes) called artificial neurons [ 21 , 59 , 60 ]. The ANN computational system consists of three layers: the input layer, which contains input neurons that represent input data; the hidden layer, which contains a specific number of hidden neurons; and the output layer, which consists of the output data (the number of neurons is equal to the number of desired outputs).…”
Section: Resultsmentioning
confidence: 99%
“…ANN is a rapid and reliable method broadly used for solving complex problems by using various algorithm architectures [ 33 , 58 , 59 ]. Consequently, this modeling approach can be used as a prediction instrument for determining nonlinear relationships between input and output results for different manufacturing processes [ 59 ].…”
Section: Introductionmentioning
confidence: 99%